Agroecological sustainability assessment of two production systems with an emphasis on vegetables in Venezuela - Silva-Laya, Silvia Josefina; Pérez-Martínez, Simón; Álvarez-Del-Castillo, Javier (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The objective of this research was to evaluate the sustainability of two agroecological production systems for vegetable and medicinal plants in a peri-urban area (NUDES-La Limonera) and an agricultural area (FIRP) in Venezuela. Descriptive observations were made for eleven months between 2014 and 2015. A sociodemographic questionnaire was applied, and sixteen sustainability indicators were quantified for the dimensions: ecological (IE), economic (IK), and sociocultural (ISc), with previously published methodologies. NUDES-La Limonera is part of a political project from the National Executive Branch, and its sustainability indicators reached less favorable levels, especially for EI (conservation of life in the soil and dependence on external inputs) and IK (food self-sufficiency, role of family labor, economic risk and diversity of products for sale). ISc contained indicators that showed greater strength (particularly the density of relationships with other groups); however, the satisfaction of basic needs, such as housing, was not met because the land is not  owned (only guardianship and custody). The FIRP is part of an initiative of organized producers for the agricultural diversification of the Venezuelan Andes. It presented the most favorable values for sustainability in the three dimensions. It is worth mentioning that, for IK, productivity and profitability were optimal in the last three analyzed years and, for ISc, the land was owned. The results evidenced  the importance of synergies that are generated within interactions in productive systems as a sustainability strategy.